Fostering Differentiated Instruction through AI Tools: Perceptions of In-Service Teachers in Morocco - Abdelmounim Lagmidi; Abdessallam Khamouja; Belal Amedyaz; Hind Brigui (Yayasan Visi Intan Permata, 2026)
While educational systems worldwide are rapidly embracing Artificial Intelligence (AI) tools, getting a deeper understanding of the way teachers perceive it is of great importance for a well-informed integration. Educational reforms in Morocco continuously emphasize inclusive practices and the inclusion of digital tools, which makes AI adaptation as a transformative tool in classroom instruction. This study investigates the perceptions of Moroccan in-service teachers regarding the use of AI tools to enhance Differentiated Instruction (DI). Adopting a quantitative design, data were collected through a questionnaire that was administered to a sample of 213 teachers across various Moroccan regions. The findings reveal a generally positive stance regarding the implementation of AI tools in promoting DI. However, this promising support comes with notable challenges, namely a lack of training, insufficient infrastructure, and the digital divide. This study contributes to existing literature by showing in-service teachers’ attitudes towards the integration of AI in assisting DI practices. It also offers practical recommendations for policymakers, curriculum designers, and teacher trainers seeking to incorporate inclusive practices through AI integration.